KINETICS OF ANTIBODIES AGAINST PRRSV IN WEANING, FATTENING AND FINISHING PIGS IN A FARM IN LIMA, PERU - Calcina I., Juan (2014)
The objective of the present study was to evaluate the kinetic of antibodies againstthe Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) in 30 of a group of200 pigs in a commercial farm in Lima, Peru. Blood samples were collected at 32, 61 and 135days of age for detecting antibodies against PRRSV by indirect ELISA. In addition, the occurrence of respiratory clinical signs was daily recorded in the total group of 200animals including the 30 animals of the study. The 26.7% (8/30) of pigs had antibodiesagainst PRRSV at 32 days of age and only one at 61 days of age, while 96.7% (29/30) hadantibodies against PRRSV at 136 days of age with S/P values between 0.4 and 2.0. Nonrespiratory problems were recorded. The presence of antibodies and age of animals wasstatistically associated (p<0.05).